2005
DOI: 10.1289/ehp.7447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Pollution on Heart Rate Variability: The VA Normative Aging Study

Abstract: Reduced heart rate variability (HRV), a marker of poor cardiac autonomic function, has been associated with air pollution, especially fine particulate matter [< 2.5 μm in aerodynamic diameter (PM2.5)]. We examined the relationship between HRV [standard deviation of normal-to-normal intervals (SDNN), power in high frequency (HF) and low frequency (LF), and LF:HF ratio] and ambient air pollutants in 497 men from the Normative Aging Study in greater Boston, Massachusetts, seen between November 2000 and October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
277
5
20

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 313 publications
(318 citation statements)
references
References 48 publications
16
277
5
20
Order By: Relevance
“…All of them found that an increase in PM 2.5 or in PM 10 , alone or combined with other pollutants like ozone, were associated with a reduction of the SDNN and of the rMSSD, only one study informed an increase of this last index (Gold et al, 2000). Studies in which frequency domain indexes were used also found this association, particularly of the HF of a parasympathetic-related index (Liao et al, 1999;Holguı´n et al, 2003;Park et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them found that an increase in PM 2.5 or in PM 10 , alone or combined with other pollutants like ozone, were associated with a reduction of the SDNN and of the rMSSD, only one study informed an increase of this last index (Gold et al, 2000). Studies in which frequency domain indexes were used also found this association, particularly of the HF of a parasympathetic-related index (Liao et al, 1999;Holguı´n et al, 2003;Park et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Most air pollution research has measured the exposure with fix monitors, in some cases data were taken from the environmental monitor network, which is known to be a good estimate but may be altered by weather conditions such as wind, rain or RH (Pope et al, 1999, Gold et al, 2000, Park et al, 2005. Other studies have used fixed indoor monitors (Liao et al, 1999;Holguı´n et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous community-based cross-sectional study, we reported that particulate matter o2.5 mm in aerodynamic diameter (PM 2.5 ), ozone (O 3 ), and BC were associated with reduced cardiac autonomic function, measured by HRV (Park et al, 2005). In this paper, we examine whether pollution originating in different locations has different associations with HRV using data from our previous study (Park et al, 2005) and from a trajectory cluster analysis.…”
Section: Introductionmentioning
confidence: 98%
“…In this paper, we examine whether pollution originating in different locations has different associations with HRV using data from our previous study (Park et al, 2005) and from a trajectory cluster analysis.…”
Section: Introductionmentioning
confidence: 99%